Cost determinants and financing of health expenditure: Evidence from India - Sakshi, Sakshi; Sharma, J. N. (International journal of economic perspectives, 2025)
Despite achieving sustained economic growth, India continues to face challenges in public health financing and outcomes. India’s public health spending, at just 2–3% of GDP, lags global norms and contributes to persistent gaps in healthcare infrastructure and access. This study analyses annual data from 1991–2022 to examine the determinants of per capita public and private health expenditures. Using the autoregressive distributed lag (ARDL) model with FMOLS & DOLS for robustness, results confirm stable long-run relationships. Per capita public expenditure is strongly influenced by out-of-pocket spending, urbanization, and population, while per capita private expenditure responds more to life expectancy and demographic change. The findings shed light on India’s dual health financing structure.